The Effect of Teacher Personality Competence and School Climate on the Character of Junior High School Students in Solok Regency - Eldasisca Dwapatesty; Hadiyanto; Irsyad; Sulastri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by the results of the author's observations regarding the effect of teacher personality competence and school climate on the character of junior high school students in Solok Regency which shows that it is still not good and the character of students is still low. The purpose of this study was to obtain data and information regarding (1) whether there is an effect of teacher personality competence on the character of junior high school students in Solok district, (2) whether there is an influence of school climate on the character of junior high school students in Solok district, ( 3) is there an effect of the teacher's personality competence and school climate together on the character of junior high school students in Solok Regency.This research is a correlational quantitative research with the type of "associative" research. The population is 1446 teachers and the sample is determined using the slovin formula with an error rate of 10% with the Proportionate Stratified Random Sampling technique to obtain 146 teachers. The research instrument uses a questionnaire with a Likert scale which has 5 alternative answers. Before the questionnaire was used, trials were carried out to determine its validity and reliability. Data collection techniques were carried out using questionnaires. Data analysis techniques were performed by data description, requirements analysis test, multiple linear regression test and hypothesis testing. The results of the data analysis show that there is a significant influence between the teacher's personality competence on the character of students with tcount>ttable (5.163>1.977). There is a significant influence between school climate and student character with tcount>ttable (2.339>1.977). There is a significant influence between teacher personality competence and school climate on student character with a value of Fcount>Ftable (26.676 > 3.06), so there is a significant influence between teacher personality competence and school climate together on student character. The regression table shows a constant value of 43.289 and a regression coefficient of the X1 variable of 0.411 and a regression coefficient of the X2 variable of 0.178. So the multiple linear regression equation used is 43.289+0.411X1+0, 178X2+e. In the test of the coefficient of determination, it was found that r² = 0.272 which indicates that the determination of the incentive and school climate variables on teacher work motivation is 27.2%.